2023
DOI: 10.1002/mcf2.10244
|View full text |Cite
|
Sign up to set email alerts
|

Demography of Oysters Pre‐ and Postcollapse in Apalachicola Bay, Florida, Using Stage‐Based Counts

Abstract: The collapse of oyster populations and the fisheries they support has been a worldwide phenomenon, but studies of oyster demography in situ prior to and after the collapse have been rare. We used time series of stage‐based counts of eastern oysters Crassostrea virginica in Apalachicola Bay, Florida, to help understand how abundance and demographic rates may have changed in the decade after the 2012 collapse relative to the period before the collapse. We relied on a Bayesian hierarchical model in which the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Alternative hypotheses related to oyster population decline, including cascading predatory responses (Kimbro et al 2017), recruitment overfishing, discard mortality, virulent disease (known or unknown), freshwater inflow, climate change, or some combination of these, remain largely unassessed and impossible to address with available data. The reasons for the 2012 collapse and the decade-plus period of low oyster abundance are uncertain (Camp et al 2015;Kimbro et al 2017;Pusack et al 2018;Johnson et al 2023) and have been debated in courts as high as the U.S. Supreme Court (Kelly 2019; Barnett 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative hypotheses related to oyster population decline, including cascading predatory responses (Kimbro et al 2017), recruitment overfishing, discard mortality, virulent disease (known or unknown), freshwater inflow, climate change, or some combination of these, remain largely unassessed and impossible to address with available data. The reasons for the 2012 collapse and the decade-plus period of low oyster abundance are uncertain (Camp et al 2015;Kimbro et al 2017;Pusack et al 2018;Johnson et al 2023) and have been debated in courts as high as the U.S. Supreme Court (Kelly 2019; Barnett 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It also coincided with high levels of oyster predators, such as crabs and conchs; parasites, such as worms, snails, and sponges (Figure 4); and pathogens, such as Perkinsus, a group of parasitic protists (single-celled organisms) that infect certain marine animals. Research showed the oyster population collapse was likely related to decreased survival of juvenile oysters (Pine et al 2015;Johnson et al 2023). Additionally, results from field experiments demonstrate that as the salinity in Apalachicola increased, so did the presence of an oyster predator called oyster drills (Kimbro et al 2017).…”
Section: Apalachicola Baymentioning
confidence: 99%
“…It is possible that this lower survival of juvenile oyster was made worse by high salinity or other environmental conditions (Camp et al 2015;Kimbro et al 2017). However, links between salinity and oysters are not clear (Fisch and Pine 2016), and juvenile survival appears to have remained low in the 2012-2022 period despite variable and more normal water conditions (Johnson et al 2023). Increasingly it seems that the oyster population in Apalachicola Bay experienced a shift to a much lower (and less valuable) population level (Johnson, Pine, and Camp 2022).…”
Section: Apalachicola Baymentioning
confidence: 99%
See 1 more Smart Citation